LANGUAGE LEARNING STRATEGIES FOR ENGLISH ACHIEVEMENT IN VOCATIONAL HIGH SCHOOL STUDENTS - Fataa, Muhammad Amirul; Toyyibah, Toyyibah (FKIP UNISKA, 2024)
Indonesian students' average English proficiency is declining. The decline in English skills among Indonesian students is due to students' learning difficulties. Appropriate English language learning strategies (LLS) can improve students' academic performance. This study aims to find out the students' dominant LLS, then the students' learning achievement, and find out the distribution of students' LLS in the student's achievement. This study uses a quantitative method with a survey approach. The population of this study was tenth-grade students of SMK PGRI 1 Kota Kediri. The instruments used in this study were questionnaires and tests. The data show differences in the use of language learning strategies among students. The mean score for LLS use was 2.62. The second data is students' achievement. From the data, the highest score obtained by a student was 100, the lowest score was 16, and the overall average score was 46.48. The second data is students' achievement. The highest score obtained by a student was 100, the lowest score was 16, and the overall average score was 46.48. From the data, students who achieved perfect category grades mainly used metacognitive and social strategies. Students who primarily use compensation and memory strategies tend not to fall into the